Application of Ethical Standards in Patient Information Management: Legal Perspectives and Medical Practice - Ery Rachma Firsanti; Hj. Yeti Kurniati; Hj. Hernawati RAS (Formosa Journal of Social Sciences (FJSS), 2023)
This study investigates the ethical dilemmas that arise in the management of patient information in daily clinical practice, with a focus on the balance between the need for rapid access to medical information and the protection of patient privacy. Through case study analysis, surveys of health practitioners, and collaboration between health and legal institutions, this research aims to understand how doctors and medical personnel understand, confront, and overcome these ethical dilemmas in clinical decision making